2010
DOI: 10.1016/s0929-6646(10)60104-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of Head-up Tilt Table Testing in Children

Abstract: HUT can be safely performed with a high specificity in children, with the sensitivity of HUT improved by isoproterenol. Therefore, a positive response to treatment is reassuring to the physician and family. NCS is generally a self-limited condition despite a high recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 12 publications
0
17
0
3
Order By: Relevance
“…In that study, most of the patients accepted non-pharmacological treatment (education and increasing fluid and salt intake) and only 15.4% accepted short-term pharmacological treatment (β blocker, diphenidol). During follow-up, the overall recurrence rate was 30.8%, but most of the patients experienced less severe syncopal episodes and only had premonitory symptoms (26). Our study indicated that combination of beta-blocker therapy with increasing salt and water intake decreased the recurrence rate of syncope.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In that study, most of the patients accepted non-pharmacological treatment (education and increasing fluid and salt intake) and only 15.4% accepted short-term pharmacological treatment (β blocker, diphenidol). During follow-up, the overall recurrence rate was 30.8%, but most of the patients experienced less severe syncopal episodes and only had premonitory symptoms (26). Our study indicated that combination of beta-blocker therapy with increasing salt and water intake decreased the recurrence rate of syncope.…”
Section: Discussionmentioning
confidence: 59%
“…Lai et al examined 79 patients below 18 years of age who underwent head up tilt test for evaluation of syncope or presyncope. Among the patients, 69% had mixed type, 28% had cardioinhibitory, 3% had vasodepressor, and 3.7% had asystole syncope attacks (26). Yilmaz et al also performed a study on 150 patients aged between 8 and 18 years who were referred to their clinic due to syncope.…”
Section: Discussionmentioning
confidence: 99%
“…The POTS diagnosis is more confusing in the case of pediatric patients. However, we considered inclusion criteria of Thieben et al9) to be more reasonable and suited to the actual definition of POTS for the following reasons: Previous studies on orthostatic intolerance have reported that the sensitivity of the tilt-table test is low16). Wieling17) also reported that the initial phase of active standing caused more drastic hemodynamic changes than the tilt-table test, which clearly explains patient's symptoms of orthostatic intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Returning the patient quickly to the supine position can sometimes promote consciousness recovery. For children 6-18 years old, HUTT has high specificity, and no severe HUTT-related complications have been found [31]…”
Section: Safety Issue Of Huttmentioning
confidence: 96%